Evaluating The Implementation of The Maputo Protocol in The Protection of Women's Rights in Kenya - Numadi, Katong Ragawi (Global Strategis, 2024)
The Maputo Protocol is the most progressive provision specified by the African Nations regarding the importance of women's protection. The content of the protocol was agreed upon by the board of the African Union in Maputo, Mozambique, in July 2003. Entering twenty years of implementation in 2023, 44 of 55 governments of the African countries have committed to protecting women's rights based on the protocol's provisions. Kenya has only ratified the protocol since 2010, which is relatively new compared to the other African countries. This research aims to explain and evaluate the implementation of the Maputo Protocol in Kenya from its ratification in 2010 until the end of 2023. This research uses a qualitative method to gain a comprehensive understanding by analyzing any information from official documents, previous research, related journals, news reports, and other secondary sources. The results show a huge commitment from the government, agencies, institutions, and the Kenyan community to improve women's conditions by supporting the protocol's implementation. As a result, women's rights in the country have shown some progress in recent years. However, some problems related to gender inequality still exist and need to be the primary concern of the government and the people of Kenya. Keywords: Maputo Protocol, Women’s Rights, Kenya   Protokol Maputo merupakan aturan mengenai perlindungan perempuan yang berlaku di kawasan Afrika. Pemberlakuan protokol disepakati oleh negara-negara anggota African Union di Maputo, Mozambik, pada Juli tahun 2003. Memasuki dua puluh tahun implementasi Protokol Maputo pada tahun 2023, sebanyak 44 dari 55 negara Afrika telah menyatakan komitmennya untuk melindungi hak-hak perempuan sebagaimana yang diatur di dalam ketentuan protokol. Kenya merupakan salah satu negara yang baru meratifikasi Protokol Maputo pada tahun 2010. Penelitian ini bertujuan untuk menjelaskan dan mengevaluasi implementasi Protokol Maputo di Kenya sejak meratifikasi pada tahun 2010 sampai 2023. Penelitian ini menggunakan metodologi kualitatif dalam rangka memperoleh pemahaman komprehensif dengan menganalisis berbagai informasi terkait dari dokumen kenegaraan, penelitian sebelumnya, jurnal, berita, dan sumber-sumber sekunder lainnya. Secara umum, diketahui bahwa sejak meratifikasi Protokol Maputo, Kenya telah menunjukkan beberapa progres perlindungan hak asasi perempuan. Kendati demikian, berbagai permasalahan mengenai ketidaksetaraan gender masih terjadi dan patut mendapatkan perhatian serius dari pemerintah dan komunitas masyarakat di Kenya.  Kata-kata Kunci: Protokol Maputo, Perlindungan Perempuan, Kenya